Perkembangan Praimplantasi Embrio Mencit dengan Materi Genetik yang Berasal dari Parental, Maternal, dan Inti Sel Somatik (PRE-IMPLANTATION DEVELOPMENT OF MOUSE EMBRYO WITH GENETIC MATERIAL DERIVED FROM PARENTAL, MATERNAL AND SOMATIC CELL NUCLEUS) - Murti, Harry; Fahrudin, Mokhamad; Agus Setiadi, Mohamad; Setiawan, Boenjamin; Boediono, Arief (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
Cloned embryo and parthenogenetic embryo are a potential source of stem cells for regenerativemedicine. Stem cells derived from those embryos are expected to overcome the ethical issues to the use offertilization embryos for therapeutic purposes. The pre-implantation development is a critical step fordeveloping embryos reach the blastocyst stage. The objectives in vivo of this research are to produce mousecloned embryo, parthenogenetic embryo, and fertilized embryo and to study stages of  in vitro pre-implantation development culture. In vivo fertilized embryos, mouse oocytes, and cumulus cells were usedin this study. Treatment was performed on female mice superovulated with PMSG and hCG injections.Two-cell stage of in vivo fertilized embryos were collected on the second day post hCG injection. Clonedembryos were produced through Somatic Cell Nuclear Transfer (SCNT), which included enucleation, nucleartransfer and artificial activation. Parthenogenetic embryos were produced with artificial activationtechnique. The result of the research indicated that SCNT application was able to produce cloned embryos which could develop to blastocyst stage (3,2%). In addition, artificial activation of oocytes could produceparthenogenetic embryos which were able to develop up to the blastocyst stage (8,6%). In conclusion,efficiency level of parthenogenetic embryos that is able to reach the blastocyst stage was higher than in thecloned embryos. Fertilized embryos shows a better development and more efficient compared to in vitrocloned embryos and parthenogenetic embryos cultures.
Keywords: embryo, fertilization, cloned, parthenogenetic, in vitro culture